Trauma-Induced Psoriatic Arthritis: A Deep Köbner Phenomenon - Mima, Yoshihito; Yamamoto, Masako; Nishida, Naoki; Norimatsu, Yuta; Iozumi, Ken (Case reports in dermatology, 2025)
Introduction: Psoriasis is a chronic systemic inflammatory disorder resulting from complex interactions between genetic and environmental factors. In addition to cutaneous manifestations, psoriasis is associated with psoriatic arthritis (PsA). Among the recognized mechanisms of disease exacerbation, the Köbner phenomenon (KP) plays a crucial role. KP refers to the appearance of new psoriatic lesions on previously healthy skin following trauma. A deeper variant of this phenomenon, the deep Köbner phenomenon (DKP), involves severe trauma triggering systemic inflammation, including the onset of PsA. Trauma-induced DKP represents unique disease mechanisms, linking external mechanical stress to immune-mediated joint pathology. Case Presentation: We present a case of a 60-year-old male with psoriasis, who initially responded well to ixekizumab, an IL-17A inhibitor but subsequently developed PsA following a wrist injury. The PsA exacerbation was attributed to increased mechanical stress from daily activities and rehabilitation efforts. Adjustments were made to rehabilitation intensity and joint movement restrictions, leading to gradual symptom improvement over 3 months without intensifying biological therapy. Conclusion: This case highlights the pathophysiological relationship between trauma, DKP, and PsA. The rapid onset of PsA following trauma suggests that inflammatory mediators and neuropeptides triggered by DKP play significant roles. Given that rehabilitation plays crucial roles in recovery but may also exacerbate symptoms if improperly managed, tailored rehabilitation strategies are essential in managing trauma-induced PsA. This case also underscores the importance of comprehensive management, including biological therapy and personalized rehabilitation approaches. Further studies are needed to optimize inflammation control and joint function in patients experiencing post-trauma PsA.